KEMAMPUAN MEMAHAMI TEKS ANEKDOT SISWA KELAS X SMK PERPAJAKAN RIAU - Kresmanitalia, Kresmanitalia; Charlina, Charlina; Septyanti, Elvrin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the level of ability to understand anecdotal texts, and determine the differences in the ability to understand anecdotal texts per class, X grade students of Riau Taxation Vocational School. This research method is descriptive quantitative. The population in this study amounted to 92 people and the samples obtained using the Slavin formula were 75 people. The data collection technique used the essay test technique. The test is in the form of questions about understanding the structure and messages in anecdotal texts. The data analysis technique used the Normality Test through the Lilifors Test. Then rhe Chi Square Test of one sample to determine the category of students understanding ability. Kruskall-Wallis test to determine the ability of students per class. The conclusion is that the ability to understand anecdotal texts of class X students of Riau Tax Vocational High School is categorized as very low and there is no difference in the ability of students of class X of Riau Tax Vocational school.Key Words: Understanding Ability, Anecdotal Text, Class X Students